Lã ovina de descarte funcionalizada com nanopartículas de ouro fitogênicas: síntese e avaliação catalítica - (:unkn) unknown (Universidade Federal do Pampa, 2026)
In Brazil, especially in the Southern Region, wool still holds relevance; however, the focus of sheep farming has increasingly shifted toward meat production, reducing its value. In Rio Grande do Sul, despite the strong tradition associated with breeds such as Corriedale and Ideal (Polwarth), the activity has been losing ground due to competition from synthetic fibers and the higher economic return of meat. As a result, wool disposal has intensified, often being treated as waste and subjected to inadequate practices such as burning or burial, generating negative environmental impacts. In this context, the present work proposes the valorization of waste wool as a support for the immobilization of biogenic gold nanoparticles, with a focus on the degradation of organic contaminants in aqueous media. Wool exhibits favorable properties, such as high porosity, large surface area, and the presence of functional groups (amino, carboxyl, and thiol), which promote nanoparticle fixation and contribute to catalytic efficiency. The anchoring of gold nanoparticles onto the wool fiber is rationalized by the HSAB (Hard and Soft Acids and Bases) theory, proposed by Ralph G. Pearson, which predicts preferential interactions between species of similar “softness.” In this system, nanoscale gold behaves as a soft acid, while the thiol (-SH) groups of wool keratin act as soft bases. The synergistic soft–soft interaction favors the formation of robust Au–S bonds, promoting efficient and durable immobilization of the nanoparticles within the fibrous matrix. Consequently, enhanced material stability, suppressed leaching, and improved catalytic performance are observed. The gold nanoparticles were synthesized via a green route using an aqueous extract of Baccharis dracunculifolia DC. The wool functionalized with gold nanoparticles was characterized by FTIR-ATR, XRD, UV-Vis, SEM, and EDX. Subsequently, the hybrid material Wool@AuNPs/Extract acted as a heterogeneous catalyst in the reduction of methylene blue, demonstrating an efficient, low-cost, and sustainable alternative for the treatment of contaminated water, as well as reusability for up to five cycles without significant loss of performance.
Waste sheep wool functionalized with phytogenic gold nanoparticles: synthesis and catalytic evaluation
Keywords: Fibra animal; Suporte biofuncional; Ouro nanométrico; Baccharis dracunculifolia DC; Catálise heterogênea; Animal fiber; Biofunctional support; Nanometric gold; Baccharis dracunculifolia DC extract; Heterogeneous catalysis; ENGENHARIAS